Evaluation of pharmacovigilance concepts among healthcare professionals in Davangere, Karnataka, India - Shastry, Shashank; M., Santhosh Kumar (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Adverse drug reactions are one of the leading causes of morbidity and mortality worldwide. Timely detection and reporting of adverse drug events through pharmacovigilance is the best tool we have to prevent adverse drug reaction. One of the major reasons for underutilization of pharmacovigilance in India is deficit in awareness, attitude and practice of pharmacovigilance. The objective of this study was to assess these parameters among healthcare professionals in our hospital. Methods: 200 health care professionals (post graduate students, undergraduate students, interns and nurses) took part in the study. A pre-designed questionnaire structured to obtain information on pharmacovigilance was used for evaluation. Questionnaire also enquired on factors that deter respondents from reporting. Results: Among undergraduates, the satisfactory responses for knowledge, awareness and practice of pharmacovigilance were 12%, 72% and 42% respectively and for postgraduates it was 52%, 48% and 26% respectively. For interns it was 4%, 38% and 8 % respectively and nurses 8%, 18% and 26% respectively. Only 1% of undergraduates and 14% of postgraduates showed satisfactory responses to all three categories evaluated. Undergraduate students had a significantly higher awareness scores among the categories (p<0.05). When it comes to knowledge and practice there was not much differences between groups. Lack of time to report was the most cited factor across all categories discouraging reporting. Conclusions: Results are encouraging among undergraduate students, but not significantly better than postgraduates. The poor performance among interns and nurses is due to lack of awareness. A strong basic foundation course regarding pharmacovigilance in academics will help in effective implementation of pharmacovigilance.